Answer:
Step-by-step explanation:
Let x be the length of each side of square.
Since the perimeter of the square is 4 times the length of each side, so perimeter of our given circle will be 4x.
We have been given that the perimeter of a square garden is to be at least 30 feet but not more than 64 feet.
This means the perimeter of the garden should we greater than or equal to 30 feet and less than or equal to 64 feet.
We can represent this information in an equation as:
Let us divide our inequality by 4 to solve for x.
We can represent our answer in interval notation as:
Therefore, the length of the square's side can be any number between 7.5 feet and 16 feet including both 7.5 and 16 as well.
Answer:
Step-by-step explanation:
4x - 2y = 5 -------------------------------(1)
y = 3x - 1 ----------------------------------(2)
Put Eq. (2) in (1)
4x - 2(3x-1) = 5
4x - 6x + 1 = 5
-2x + 1 = 5
Subtracting 1 to both sides
-2x = 5 - 1
-2x = 4
Dividing both sides by -2
x = 4 / -2
x = -2
Hope this helped!
Answer:
X = 7
Step-by-step explanation:
Please mark brainliest.
The total change in altitude= 960ft.
Step-by-step explanation:
Rate at which balloon descend = 320 ft per minute
Time = 3 mins
Total height descended = 320 x 3
= 960 ft.
The total change in altitude= 960ft.
The coordinates of point O of the given Reflection is; 5, 5
The coordinates point is missing and so I have attached it.
Now, from the question, we are told that N is the reflection of B and O is the reflection of C. Thus, from the attached image, drawing a line to the right of N and a vertical line below C, the point of intersection of these two lines would give us the location of point O.
Drawing a line to the right of N and a vertical line below C, the point of intersection of these two lines which is point O has coordinates at (5,5).
Read more about Point Coordinates at; brainly.com/question/17206319
#SPJ5
Equation B: y = 3x + 1
Which of the following is a step that can be used to find the solution to the set of equations?
2x + 4 = 3x + 1
2x = 3x + 4
2x + 4 = 3x
2x + 1 = 3x + 4
Answer:
a
Step-by-step explanation: